Estimation of effective moduli of composites through self-consistent scheme - Kavin Raj Nedumaran (2017)
The purpose of this project is to extend Budiansky’s (1965) self-consistent method and inclusion-matrix-composite theory of Christensen and Lo (1979) to the development of a new method that would serve as an alternative to Tang’s (2017) averaging procedure in associating structural properties at the macroscopic level with microscopic crack distributions. This method involved the development of a numerical version of the self-consistent scheme. The numerical simulations consisted of the estimation of the effective moduli of various composite geometries, through an iterative process of strain energy equivalence, under 2D plane strain conditions. The iterative process involved the assumption of the total sum of elemental strain energy of the microscopic model, S.E.MICRO, to be approximately equal to the total sum of elemental strain energy, of the macroscopic model, S.E.MACRO. The finite element method was specifically used to develop the numerical simulation. The numerical simulations were carried out through Mechanical ANSYS Parametric Design Language (APDL), a Finite Element Analysis software. This investigation, which examined how changes in the dimensionless inclusion length-matrix width, a/b, affected effective elastic modulus, EEFF, values, was carried out through a parametric study. This investigation might not be directly applying the theory of the self-consistent scheme, but it is however treated in the ‘spirit’ of the method.